Дослідження очисника вороху коренебульбоплодів від залишків - Василюк, В. І.; Vasilyuk, Volodymyr (КНТУ, 2013)
Створено новий очисник вороху коренебульбоплодів спірального типу, експериментальна установка і результати польових досліджень розробленого робочого органу. Наведено експериментальні залежності якісних показників роботи очисника від основних конструктивних і кінематичних його параметрів. Perfection of cleansing workings organs of kartoplezbiral'nikh machines and diminishing of content of soil in the weekend of vorosi, which is taken out from the field. it the considerable improvement of the state of environment will be provided. Constructive developments of a new purifier of potato heap of spiral type, experimental installation and results of field researches of the developed working body are presented. Experimental relations of qualitative indexes of activity of a purifier to the main constructive and kinematic parametres are fetched.
Research of the purifier of heap potatos
Keywords: картопляний ворох; картоплезбиральна машина; спіральний сепаратор; potato heap; the potato harvester; a spiral separator